Transcriptomics-based characterization of the immuno-stromal microenvironment in pediatric low-grade glioma - Meik Körner; Michael Spohn; Ulrich Schüller; Michael Bockmayr (OncoImmunology)
Immunologic treatment options are uncommon in low-grade gliomas, although such therapies might be beneficial for inoperable and aggressive cases. Knowledge of the immune and stromal cells in low-grade gliomas is highly relevant for such approaches but still needs to be improved. Published gene-expression data from 400 low-grade gliomas and 193 high-grade gliomas were gathered to quantify 10 microenvironment cell populations with a deconvolution method designed explicitly for brain tumors. First, we investigated general differences in the microenvironment of low- and high-grade gliomas. Lower-grade and high-grade tumors cluster together, respectively, and show a general similarity within and distinct differences between these groups, the main difference being a higher infiltration of fibroblasts and T cells in high-grade gliomas. Among the analyzed entities, gangliogliomas and pleomorphic xanthoastrocytomas presented the highest overall immune cell infiltration. Further analyses of the low-grade gliomas presented three distinct microenvironmental signatures of immune cell infiltration, which can be divided into T-cell/dendritic/natural killer cell-, neutrophilic/B lineage/natural killer cell-, and monocytic/vascular/stromal-cell-dominated immune clusters. These clusters correlated with tumor location, age, and histological diagnosis but not with sex or progression-free survival. A survival analysis showed that the prognosis can be predicted from gene expression, clinical data, and a combination of both with a support vector machine and revealed the negative prognostic relevance of vascular markers. Overall, our work shows that low- and high-grade gliomas can be characterized and differentiated by their immune cell infiltration. Low-grade gliomas cluster into three distinct immunologic tumor microenvironments, which may be of further interest for upcoming immunotherapeutic research.